Female Off-Farm Employment and Fertility Timing in Rural China - Shen, Zheng; Zhao, Zhao; Ren, Qisheng; Yan, Mingwei (Frontiers in Public Health, 2022)
Background: Advanced maternal age is associated with fetal outcomes such as higher risks of birth defects and very low birth weight. Off-farm employment is an important factor in fertility transition in many developing countries. This study investigated the association between off-farm employment and fertility timing among Chinese rural women. Method: Using data from the China Labor-force Dynamics Survey (CLDS), we employed the ordinary least squares and instrumental variable approaches to estimate the effect of female off-farm employment on fertility timing decisions as well as the differences in the effect across groups. Results: The results show that off-farm employment participation is significantly associated with a later age at first birth, and the effect is stronger for women participating in wage employment than in off-farm self-employment. The delayed effects on fertility timing are also more pronounced for less-educated women and low-income families, implying a heterogeneous effect in terms of women’s socioeconomic status. Conclusion: Studies of the relationship between women’s off-farm employment and fertility timing in rural areas of developing countries remain limited. This study provides important insights on this topic, and it lends support to efforts to design effective policies and practices to facilitate female employment, childbearing, and health promotion.